Prevalence of infectious bronchitis and Newcastle disease virus among domestic and wild birds in H5N1 outbreaks areas - Zekiba Tarnagda; Issaka Yougbare; Adele Kam; Marc Christian Tahita; Jean Bosco Ouedraogo (Journal of Infection in Developing Countries)
Introduction: The first H5N1 outbreak in Burkina Faso was reported to the World Organization for Animal Health on 3 April 2006. This study aimed to determine the prevalence of avian influenza virus, infectious bronchitis virus, and Newcastle disease virus among domestic and wild birds in highly pathogenic avian influenza (HPAI) H5N1 outbreaks areas.